FABP4 in obesity-associated carcinogenesis: Novel insights into mechanisms and therapeutic implications - Liu, Shujie; Wu, Dong; Fan, Zhiyao; Yang, Jian; Li, Yongzheng; Meng, Yufan; Gao, Changhao; Zhan, Hanxiang (Frontiers in Molecular Biosciences, 2022)
The increasing prevalence of obesity worldwide is associated with an increased risk of various diseases, including multiple metabolic diseases, cardiovascular diseases, and malignant tumors. Fatty acid binding proteins (FABPs) are members of the adipokine family of multifunctional proteins that are related to fatty acid metabolism and are divided into 12 types according to their tissue origin. FABP4 is mainly secreted by adipocytes and macrophages. Under obesity, the synthesis of FABP4 increases, and the FABP4 content is higher not only in tissues but also in the blood, which promotes the occurrence and development of various cancers. Here, we comprehensively investigated obesity epidemiology and the biological mechanisms associated with the functions of FABP4 that may explain this effect. In this review, we explore the molecular mechanisms by which FABP4 promotes carcinoma development and the interaction between fat and cancer cells in obese circumstances here. This review leads us to understand how FABP4 signaling is involved in obesity-associated tumors, which could increase the potential for advancing novel therapeutic strategies and molecular targets for the systematic treatment of malignant tumors.